2015
DOI: 10.1007/s10048-015-0467-8
|View full text |Cite
|
Sign up to set email alerts
|

COMT Val 158 Met polymorphism is associated with nonverbal cognition following mild traumatic brain injury

Abstract: Mild traumatic brain injury (mTBI) results in variable clinical outcomes, which may be influenced by genetic variation. A single-nucleotide polymorphism in catechol-o-methyltransferase (COMT), an enzyme which degrades catecholamine neurotransmitters, may influence cognitive deficits following moderate and/or severe head trauma. However, this has been disputed, and its role in mTBI has not been studied. Here, we utilize the Transforming Research and Clinical Knowledge in Traumatic Brain Injury Pilot (TRACK-TBI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 71 publications
(75 reference statements)
1
32
0
Order By: Relevance
“…Phasic dopamine is likely to be involved in FER through mesolimbic projections toward the amygdala. In addition, although from different clinical populations, COMT Val158Met polymorphism is associated with nonverbal cognition (Winkler et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Phasic dopamine is likely to be involved in FER through mesolimbic projections toward the amygdala. In addition, although from different clinical populations, COMT Val158Met polymorphism is associated with nonverbal cognition (Winkler et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the A2 allele, may actually impart a greater risk for poor DA modulation that differs from healthy populations. While other genetic components of the DA system may influence outcomes, COMT and ANKK1 are currently the only genes with both a strong mechanistic rationale and previously documented associations with other TBI outcomes (cognition) in the literature 47,48,49 .…”
Section: Introductionmentioning
confidence: 99%
“…Catechol-o-methyltransferase (COMT) is the main regulator of dopaminergic synaptic transmission as it is an enzyme responsible for degrading dopamine (DA) (Axelrod and Tomchick, 1958;Winkler et al, 2015). Dopaminergic synaptic transmission is important for regulating cognition as low levels of DA within the PFC have been associated with deficits in executive function (Logue and Gould, 2014).…”
Section: Catechol-o-methyltransferase Val 158 Met Polymorphismmentioning
confidence: 99%
“…investigate the presence of the COMT Val 158 Met polymorphism and cognitive symptoms 6 months after injury. Using various measures of cognitive function, their results revealed that individuals with a COMT Met 158 allele had a significantly higher processing speed and the difference was associated with concussion injury severity (Winkler et al, 2015).…”
Section: Winkler and Colleagues (2015) Recruited Individuals Who Sustmentioning
confidence: 99%
See 1 more Smart Citation